2010
DOI: 10.1088/0004-637x/718/2/981
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Sigmoids as Progenitors of Coronal Jets: Is Eruptive Activity Self-Similarly Multi-Scaled?

Abstract: Observations from the X-ray telescope (XRT) on Hinode are used to study the nature of X-ray bright points, sources of coronal jets. Several jet events in the coronal holes are found to erupt from small-scale, S-shaped bright regions. This finding suggests that coronal micro-sigmoids may well be progenitors of coronal jets. Moreover, the presence of these structures may explain numerous observed characteristics of jets such as helical structures, apparent transverse motions, and shapes. In analogy to large-scal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
76
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 46 publications
3
76
0
3
Order By: Relevance
“…Recently, a self-similar AR-coronal BP jet connection was made when Raouafi et al (2010) observed micro-sigmoids at the bases of coronal jets in XRT data. The authors found that these micro-sigmoids were manifestations of merging "Jshaped" loops at scales significantly smaller than their AR counterparts (McKenzie & Canfield 2008).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, a self-similar AR-coronal BP jet connection was made when Raouafi et al (2010) observed micro-sigmoids at the bases of coronal jets in XRT data. The authors found that these micro-sigmoids were manifestations of merging "Jshaped" loops at scales significantly smaller than their AR counterparts (McKenzie & Canfield 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Such observations and dynamics, along with EUV observations of micro-sigmoids (Zheng et al 2013), point to a possible multi-scaled selfsimilarity in the ensemble of sigmoid events leading to eruptive activity. Raouafi et al (2010) concluded that if there are selfsimilarities between event properties and instability mechanisms, then the eruptions of micro-sigmoids could lead to magnetic energy dissipations and injections of helicity into the heliosphere.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations